Okra Growth and Drought Tolerance When Exposed to Varying Water Regimes at Different Growth Stages. (2018)
Drought causes severe reduction in okra [Abelmoschus esculentus (L.) Moench] yield. However, the impact of drought on okra physiology has been impeding breeding where relative degrees of tolerance need to be quantified. The okra, cv. NHAe 47-4, was exposed to 25, 50, 75, or 100% field capacity (FC) to impose water deficit for 5 or 10 days, at the vegetative (V), vegetative and reproductive (VR), or reproductive (R) stages, and effects on growth and yield, leaf relative water content (LRWC), leaf photosynthetic pigments, proline, and cysteine accumulation assessed. Simulated drought reduced LRWC, leaf chlorophyll content, biomass accumulation, and okra growth compared to the control (100% FC). The effect was more severe on plants subjected to water deficit of 10 days duration at vegetative and reproductive stages at 25% FC. Plants treated at the vegetative stage alone recovered faster than those treated at the reproductive stage alone and treatment at the two stages together. After recovery, plants exposed to water deficit at the vegetative stage alone produced more chlorophyll than the control. Okra plants exposed to water deficit produced more proline, cysteine, and carotenoids than untreated plants, with the least recorded in control, and the response varied based on duration and different FC at every growth stage. The highest values for proline and carotenoids were at 25% FC for 10 days duration at every growth stage. Plants exposed to water deficit produced more fruit than the control, especially those exposed at the vegetative stage only. Under prolonged water deficit for 10 days at the vegetative stage, there was 90.95, 70.80, and 131.18% increase in fruit yield at 25, 50, and 75% FC, respectively, compared to the control. Soil water maintained at 75% FC throughout the growing period enhanced fruit production compared to other field capacities including control. Okra response depends on water deficit severity, duration, and growth stage. Production of proline and carotenoid could be a strategy employed by okra plants for tolerance under water deficit.